(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2026)
This study explores the intricate dynamics of wholeness and individuation within the African experience as represented in Chinua Achebe’s Things Fall Apart. Drawing on Carl Jung’s theory of individuation and from postcolonial discourse, the study explores how identity is shaped within a society disrupted by colonial intrusion. It adopts a qualitative, interpretative approach, using close textual analysis to examine character development, social structures, and symbolic patterns that reflect the tension between individual identity and communal values. The study finds that wholeness in Achebe’s work is not presented as a fixed state but as a continuous process that involves balancing personal identity with cultural, spiritual, and communal commitments. The study recommends further interdisciplinary research that bridges African literature, psychology, and cultural studies, as well as comparative analyses across African texts to deepen understanding of post-colonialidentity, psychological healing, and cultural regeneration.